Building an Analytics Culture in SMEs - PAN, Gary (Institutional Knowledge at Singapore Management University, 2014)
In a commentary, SMU Associate Professor of Accounting (Education) Gary Pan wrote that SMEs must transform their culture before using analytics to improve their operations. They should first incorporate analysis into their processes and systems to build up an analytical culture. To do this, they ought to set up an effective data management system, change the way they manage, and have an open working environment. Also, leaders should set an example, and be committed to the analytical culture. Lastly, companies should not rely solely on data analysis. Associate Prof Pan said that in a changing and uncertain business environment, data and intuition need to co-exist in the decision-making process.